Can someone either help derive or give a reference to the identities in Appendix B, page 27 of this, http://arxiv.org/pdf/1111.6290v2.pdf

Here is a reproduction of Appendix B from Klebanov, Pufu, Sachdev and Safdi's $2012$ preprint (v2) 'Renyi Entropies for Free Field Theories' (from the source at arxiv.org and hoping there is no problem citing it here...(RM)).

B Useful mathematical formulae

In this section we present some useful mathematical formulae. We begin with zeta function identities.

For $0 < a \leq 1$ we have the identity $$\tag{B.1} \zeta(z, a) = \frac{2 \Gamma(1 - z)}{(2 \pi)^{1-z}} \left[\sin \frac{z \pi}{2} \sum_{n=1}^\infty \frac{\cos 2 \pi a n}{n^{1-z}} + \cos \frac{z \pi}{2} \sum_{n=1}^\infty \frac{\sin 2 \pi a n}{n^{1-z}} \right] \,$$

Taking derivatives at $z=0, -1, -2$ gives

\begin{align} \zeta'(-2, a) &= - \frac{1}{4 \pi^2} \sum_{n=1}^\infty \frac{\cos 2 \pi a n}{n^3} - \frac{1}{4 \pi^3} \sum_{n=1}^\infty \frac{(2 \log (2 \pi n) + 2 \gamma - 3) \sin 2 \pi a n}{n^3} \,, \\ \tag{B.2}\zeta'(-1, a) &= \frac{1}{4 \pi} \sum_{n=1}^\infty \frac{\sin 2 \pi q n}{n^2} - \frac{1}{2 \pi^2} \sum_{n=1}^\infty \frac{(\log (2 \pi n) + \gamma - 1) \cos 2 \pi a n}{n^2} \,, \\ \zeta'(0, a) &= \frac{1}{2} \sum_{n=1}^\infty \frac{\cos 2 \pi a n}{n} + \frac{1}{\pi} \sum_{n=1}^\infty \frac{(\log (2 \pi n) + \gamma) \sin 2 \pi a n}{n} \,. \end{align}

Two other useful identities are the regularized sums \begin{align} \tag{B.3}\sum_{n \in \mathbb{Z}} \log \left( \frac{n^2}{q^2} + a^2 \right) &= 2 \log \left[2 \sinh (\pi q |a|) \right] \,, \\ \sum_{n \in \mathbb{Z} + \frac 12} \log \left(\frac{n^2}{q^2} + a^2 \right) &= 2 \log \left[2 \cosh (\pi q |a|) \right] \,. \end{align}

These sums follow from the more general formula

$$\tag{B.4}\sum_{n \in \mathbb{Z}} \log \left( \frac{(n + \alpha)^2}{q^2} + a^2 \right) = \log \left[2 \cosh (2 \pi q |a|) - 2 \cos (2 \pi \alpha) \right] \,.$$

This relation in turn follows from the Poisson summation formula $$\tag{B.5} \frac{1}{ 2 \pi q} \sum_{n \in \mathbb{Z}} \hat f \left( \frac{n + \alpha}{q} \right) =\sum_{k \in \mathbb{Z}} e^{-i 2 \pi k \alpha} f(2 \pi q k) \,$$ applied to $$\tag{B.6}\hat f(\omega) = \log \left( \omega^2 + a^2 \right) \,.$$ For $t \neq 0$ one can simply calculate the inverse Fourier transform of $\hat f$: $$\tag{B.7}f(t) = \int_{-\infty}^\infty \frac{d\omega}{2 \pi} e^{-i \omega t} \log \left(\omega^2 +a^2 \right) = - \frac{e^{-|a|\;|t|}}{|t|} \,.$$

The case $t=0$ requires special care because the expression for $f(0)$ is divergent and requires regularization: $$\tag{B.8}f(0) = \int_{-\infty}^\infty \frac{d\omega}{2 \pi} \log \left(\omega^2 +a^2 \right) = -\frac{d}{ds} \int \frac{d\omega}{2 \pi} \frac{1}{\left(\omega^2 +a^2 \right)^s} \Biggr\rvert_{s=0} = |a| \,.$$ Using $(B.6)-(B.8)$ one can show that $(B.5)$ reduces to $(B.4)$.

  • 2
    $\begingroup$ Maybe you should copy at least one of the identities, to give the other users an idea of what kind of identity you are referring to. $\endgroup$ – M Turgeon Aug 14 '13 at 22:58

$(B.1)$ is the functional equation of the Hurwitz zeta function and Knopp and Robins' proof is available here. $$\tag{B.1}\zeta(z,a)=\frac{2\,\Gamma(1-z)}{(2\pi)^{1-z}}\left[\sin\frac {z\pi}2\sum_{n=1}^\infty\frac{\cos2\pi an}{n^{1-z}}+\cos\frac {z\pi}2\sum_{n=1}^\infty\frac{\sin2\pi an}{n^{1-z}}\right]$$

The author of your paper proposed a derivation of $(B.3)$ in reverse order since starting from $B.7)$. But let's try another derivation using the logarithm of the infinite products with $x:=\pi\,q\,|a|$ : $$\tag{1}\sinh(x)=x\prod_{k=1}^\infty \left(1+\frac {x^2}{\pi^2k^2}\right)$$ $$\tag{2}\cosh(x)=\prod_{k=1}^\infty \left(1+\frac {4\,x^2}{\pi^2(2k-1)^2}\right)$$ which may be found for example here or in the online references.

The derivation will not be direct since these products are convergent while $(B.3)$ is clearly divergent and needs some regularization. \begin{align} \frac 12\sum_{n\in\mathbb{Z}}\log\left(\frac {n^2}{q^2}+a^2\right)&=\frac 12\log\bigl(a^2\bigr)+\sum_{n=1}^\infty\log\left(\frac {n^2}{q^2}+a^2\right)\\ &=\log|a|+\sum_{n=1}^\infty\log\frac {n^2}{q^2}+\log\left(1+\frac{q^2a^2}{n^2}\right)\\ \tag{3}&=\log|a|+\sum_{n=1}^\infty\log\left(1+\frac{q^2a^2}{n^2}\right)+2\sum_{n=1}^\infty\log n-\log q\\ \end{align} The last sum at the right (as often in QFT) is heavily divergent so let's use zeta regularization to rewrite it in a finite form : $$f(z):=\sum_{n=1}^\infty\frac{\log n-\log q}{n^z}=-\zeta'(z)-\zeta(z)\log q,\quad \text{for}\ \Re(z)>1$$ (since $\;\displaystyle\frac d{dz}n^{-z}=\frac d{dz}e^{-z\log n}=-\frac{\log n}{n^z}$)

From this we deduce the 'zeta regularized sum' (using analytic extension of $f(z)$ down to $0$) : $$\sum_{n=1}^\infty\log n-\log q=\lim_{z\to 0^+}f(z)=-\zeta'(0)-\zeta(0)\log q=\frac{\log 2\pi}2+\frac 12\log q=\frac{\log 2\pi q}2$$ and get :

\begin{align} \frac 12\sum_{n\in\mathbb{Z}}\log\left(\frac {n^2}{q^2}+a^2\right)&=\log|a|+\sum_{n=1}^\infty\log\left(1+\frac{q^2a^2}{n^2}\right)+\log 2\pi +\log q\\ &=\log\left[2\,\pi q|a|\prod_{n=1}^\infty \left(1+\frac{q^2a^2}{n^2}\right)\right]\\ \\ &=\log[2\,\sinh(\pi\;q\,|a|)],\quad\text{using}\ (1)\ \text{for}\;\;q\,|a|=\frac x{\pi}\\ \end{align} Which is the first part of $(B.3)$ : $$\tag{B.3}\sum_{n\in\mathbb{Z}}\log\left(\frac {n^2}{q^2}+a^2\right)=2\;\log[2\,\sinh(\pi\;q\,|a|)]$$

I'll let you get the corresponding equation for $\cosh$.
Hoping this clarified things.


The first identity is essentially the functional equation for the Hurwitz Zeta Function. You can find a proof and associated results here, where the identity appears on page 2 of the pdf (pg 1916) as equation (2) where the $F$ series is defined on the previous page.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.